Bioelectrochemical Properties of Enzyme-Containing Multilayer Polyelectrolyte Microcapsules Modified with Multiwalled Carbon Nanotubes - Reshetilov, Anatoly; Plekhanova, Yulia; Tarasov, Sergei; Tikhonenko, Sergei; Dubrovsky, Alexey; Kim, Alexander; Kashin, Vadim; Machulin, Andrey; Wang, Gou-Jen; Kolesov, Vladimir; Kuznetsova, Iren (Membranes (Basel), 2019)
This work investigated changes in the biochemical parameters of multilayer membrane structures, emerging at their modification with multiwalled carbon nanotubes (MWCNTs). The structures were represented by polyelectrolyte microcapsules (PMCs) containing glucose oxidase (GOx). PMCs were made using sodium polystyrene sulfonate (polyanion) and poly(allylamine hydrochloride) (polycation). Three compositions were considered: with MWCNTs incorporated between polyelectrolyte layers; with MWCNTs inserted into the hollow of the microcapsule; and with MWCNTs incorporated simultaneously into the hollow and between polyelectrolyte layers. The impedance spectra showed modifications using MWCNTs to cause a significant decrease in the PMC active resistance from 2560 to 25 kOhm. The cyclic current–voltage curves featured a current rise at modifications of multilayer MWCNT structures. A PMC-based composition was the basis of a receptor element of an amperometric biosensor. The sensitivity of glucose detection by the biosensor was 0.30 and 0.05 μA/mM for PMCs/MWCNTs/GOx and PMCs/GOx compositions, respectively. The biosensor was insensitive to the presence of ethanol or citric acid in the sample. Polyelectrolyte microcapsules based on a multilayer membrane incorporating the enzyme and MWCNTs can be efficient in developing biosensors and microbial fuel cells.